Ultrasound guided abdominal plane blocks as anaesthetic technique for laparotomy in cancer patients: a case series - Rayamajhi, Anuj Jung; Bhattarai, Prajjwal Raj; Yadav, Rupesh Kumar; Paudel, Subash Chandra; Pandit, Rabin; Shakya, Vikal Chandra (Journal of Society of Anesthesiologists of Nepal, 2016)
Diagnosis and surgery pertaining cancer are increasing day by day in the developing world. Delay in diagnosis, poor socioeconomic status, and poor medical facilities are the challenge in treating these patients. Decreasing or preventing postoperative morbidity is of paramount importance in these cases. Ultrasound guided abdominal plane blocks like transversus abdominis plane block, rectus sheath block and coeliac plexus in combination with ketofol and/or dexmedetomidine sedation may be the alternative to general anaesthesia with an endotracheal tube or neuraxial block. These techniques, successfully used in our patients undergoing cancer surgeries, have a potential to decrease intensive care length of stay, decrease requirement of mechanical ventilation, early ambulation, and discharge.